Application Of Remote Sensing In Environmental Studies: A Theoretical Review - Johnny FÃ©lix FarfÃ¡n- PIMENTEL; Raul Delgado- ARENAS; Shigueki MartÃn Shimizu SANTILLÃN; Patricia Edith GuillÃ©n APARICIO; Diana Eulogia FarfÃ¡n PIMENTEL (Indonesia Strategic Sustainability, 2022)
The present research aims to perform a descriptive analysis of remote sensing and its applications in the various fields of human knowledge; although scientific and technological progress has indeed shown to reach an important development in the dynamics of natural and anthropic processes, which allows understanding their effects fully; thus, on that basis, multiple studies are conducted in the fields of spatial sciences, agriculture, geology, edaphology, oceanography, risk and disaster prevention, mining exploration, among others. Thus, this area of knowledge offers great potential for strategic planning, decision-making, and the development of environmental projects considering biodiversity and environmental sustainability. Consequently, remote sensing offers many possibilities for scientists and researchers to broaden their field of action and become familiar with the photo-interpretation of satellite images, which is very necessary for scientific work today. In the methodological part, documentary information, research works, scientific articles and environmental development projects supported the research developed. he research is of non-experimental design, descriptive design; in which a literature review was carried out in terms of remote sensing and its applications in environmental studies. The research results allowed us to obtain information on Remote Sensing in: Agriculture and soil conservation. Remote sensing has enormous potential for its application through concurrent disciplines that serve as a basis for decision making, as in the case of the agricultural sector.